(untitled) (BIRDEM Medical Journal, 2017)
Background: Basiliximab is an interleukin-2 receptor antagonist used as induction therapy in kidney transplantation and is believed to reduce acute rejection episode (ARE). Our aims were to compare the impact of basiliximab induction therapy with no induction therapy on incidence of ARE, time requirement for serum creatinine (S.Cr) to normalize after transplantation, initial post-transplant hospital stay, infection in immediate post-transplant period, chronic allograft injury and graft survival at 1 and 3 years. Methods: We retrospectively reviewed the medical records of patients who had undergone living related donor kidney transplantation in a tertiary care hospital of a developing country between July 2004 and June 2014. We selected patients who received calcineurin inhibitors, mycophenolate and prednisolone to classify as no induction therapy (n=50; group 1, receiving prednisolone, mycophenolate and cyclosporine as maintenance therapy) and induction therapy with basiliximab (n=61; group 2, receiving prednisolone, mycophenolate and tacrolimus as maintenance therapy). Results: Among the 111 study subjects, only two had experienced ARE (one from each group, p=0.889). Patients who received basiliximab had a shorter mean hospital stay (11.4±3.3 versus 13.7±5.0 days, p=0.005) and shorter mean duration for normalization of S.Cr (4.7±2.3 versus 7.3±5.6 days, p=0.002) after transplantation. There was no significant difference in incidence of infection in immediate post-transplant period (p=0.134). One year graft survival rate was better in those who received basiliximab (98.2% versus 89.4%, p=0.010) but there was no significant difference at 3 years (79% versus 74%, p=0.549). Overall incidence of chronic allograft injury was less with basiliximab (11.5% versus 36%, p=0.002) induction. Conclusions: Induction therapy with basiliximab was associated with shorter mean hospital stay, early renal function recovery, better 1 year graft survival and less overall incidence of chronic allograft injury. We have encountered minimum ARE to comment on benefit of basiliximab on ARE. Birdem Med J 2017; 7(2): 90-94